Sets of Eventual Periods of Dynamical Systems - Ali Akbar, K; Mubeena, T (Topology Proceedings, 2022)
In this paper, we discuss sets of eventual periods and obtained a class of subsets of N_0 × N which occur as sets of eventual periods for various classes of self maps, such as (1) continuous self maps of an interval, (2) continuous self maps of the plane, and (3) linear operators on vector spaces.